Selegiline Recovers Synaptic Plasticity in the Medial Prefrontal Cortex and Improves Corresponding Depression-Like Behavior in a Mouse Model of Parkinson’s Disease - Okano, Motoki; Takahata, Kazue; Sugimoto, Junya; Muraoka, Shizuko (Frontiers in Behavioral Neuroscience, 2019)
In patients with Parkinson’s disease (PD), non-motor symptoms including depression and anxiety are often recognized before motor symptoms develop. Monoamine oxidase (MAO)-B inhibitors are therapeutically effective for motor symptoms; however, their effects on non-motor symptoms in PD are yet to be fully assessed. Here, we aimed to explore the antidepressant-like effects of propargyl MAO-B inhibitors, selegiline and rasagiline, in mice treated with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) as a PD model, and to elucidate the mechanisms underlying these effects. Four repeated intraperitoneal injections of MPTP at 17.5 mg/kg to C57BL/6 mice led to a partial reduction in the number of nigrostriatal tyrosine hydroxylase-positive neurons and to the extension of immobility time during the tail suspension test (TST), without any obvious induction of motor deficits. A single subcutaneous administration of selegiline at 10 mg/kg shortened the extended immobility time of MPTP mice in the TST, without any increase in motor activities, suggesting that selegiline exerts antidepressant-like effects. In this test, rasagiline did not produce antidepressant-like effects, although the inhibitory effect of 3 mg/kg rasagiline on brain MAO activity was comparable to that of 10 mg/kg selegiline. The shortened immobility time in the TST correlated with reduced cortical dopamine turnover rates in MPTP mice treated with selegiline, but not in MPTP mice treated with rasagiline. These results suggest that MAO inhibition does not entirely account for the antidepressant-like effects of selegiline. Administration of selegiline (10 mg/kg), but not rasagiline (1 mg/kg), to MPTP mice restored the impaired long-term potentiation induced by high-frequency stimulation in the medial prefrontal cortex (mPFC), and normalized the reduced phosphorylation of Ca2+/calmodulin-dependent protein kinase IIwhich is known to be involved in neuroplasticity, in the frontal cortex. In MPTP mice, the antiparkinsonian drug pramipexole (0.3 mg/kg), a dopamine D2 and D3 receptor agonist, that has been shown to be effective in treating depression in PD, ameliorated depression-like behavior and synaptic dysfunction in the mPFC. Taken together, the antidepressant-like effects of selegiline in MPTP mice are attributable to the restoration of impaired synaptic plasticity in the mPFC, suggesting its potential for treating depression in early PD.